Treatment of massive pulmonary embolism in a soldier in Kosovo: the potential value of cardiopulmonary resuscitation and fibrinolytic therapy - Carr, Marcus E; Muller, Christian T (Military medicine, 2011)
After an 18-hour bus ride, a 29-year-old soldier complained of leg pain. Ten days later, he collapsed. After cardiopulmonary resuscitation (CPR), he revived but complained of chest pain and shortness of breath. Computed tomography revealed massive thrombus in the right pulmonary artery, emboli in the left pulmonary artery, and right ventricle ballooning. Adequate anticoagulation required repeated boluses and continuous infusion (1,600 units/hour) of heparin. Vena caval filter was not available, and possible additional clot in the legs could not be completely assessed. After no improvement in 24 hours, alteplase was given (10 mg IV bolus and 90 mg over 2 hours). At 12 hours, tachycardia, tachypnea, and dyspnea resolved and computed tomography revealed marked resolution. This case illustrates both the value of CPR and aggressive fibrinolytic therapy in patients who suddenly collapse from massive pulmonary embolism. The collapse was likely due to a saddle embolus. Chest compressions probably fractured the large clot. Although not completely reestablished, enough flow occurred for successful resuscitation. Even though delayed, fibrinolytic therapy was effective and should be considered even in patients where vena caval filter placement is not feasible and/or complete evaluation of the extremity deep venous system is not possible.
Keywords: dospělí; Tissue Plasminogen Activator; kardiopulmonální resuscitace; Yugoslavia; ozbrojené síly; Adult; Venous Thrombosis; Tomography, X-Ray Computed; Cardiopulmonary Resuscitation; Time Factors; časové faktory; lidé; Military Personnel; Jugoslávie; Pulmonary Embolism; plicní embolie; fibrinolytika; Male; Czech Republic; Česká republika; počítačová rentgenová tomografie; tkáňový aktivátor plazminogenu; mužské pohlaví; Fibrinolytic Agents; žilní trombóza; Humans